Development of a Hybrid, Interprofessional, Interactive Quality Improvement Curriculum as a Model for Continuing Professional Development. (June 2020) - Kusters, Isabelle S; Gregory, Megan E; Bryan, Jennifer L; Hysong, Sylvia J; Woodard, LeChauncy D; Naik, Aanand D; Godwin, Kyler M
Over the past 20 years, there has been an increased focus on quality improvement (QI) in health care, which is critical in achieving care that is patient-centered, safer, timelier, and more effective, efficient, and equitable. At the center of this movement is QI education, which is known to lead to learning, behavior change, and improved outcomes. However, there is a need for the development and provision of long-duration, interactive, interprofessional training in QI, to allow for in-depth learning and application of learned skills. To this end, we designed a curriculum for an established interprofessional, interactive, web-based QI fellowship for doctorally prepared clinicians. Curricular content is delivered virtually to geographically dispersed learners over a 2-year time span. The didactic curriculum and experiential learning opportunities provide learners with the foundational knowledge and practical skills to engage in—and eventually, lead—QI initiatives around the country. Evaluation of learner satisfaction and cognitive, affective, and skills-based learning has found that this model is an effective method to train geographically distributed learners. A hybrid training structure is used, where learners interact with the material through 3 distinct delivery modes: (1) virtual instruction in QI topics; (2) face-to-face training, mentorship, and the opportunity for practical application of applied knowledge and skills through the completion of QI projects; and (3) opportunities for other types of training, tailored to each learner's Individual Development Plan. This training program model holds value for QI learning in various health care settings, which are interprofessional by nature. These foundational concepts of hybrid learning to distributed learners—wherein an instructor delivers curriculum in small, face-to-face batches, interprofessional learning is supplemented in a virtual, longitudinal manner, and learners are allowed the opportunity to put skills into action for real-world problems in interdisciplinary clinical teams—can be applied in a multitude of settings, with comparatively lower time and cost expenditure than traditional training programs.